2019
DOI: 10.1021/acs.jchemed.9b00328
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Real-World Applications of Electrochemistry by Constructing a Rechargeable Lithium-Ion Battery

Abstract: The assembly and testing of a rechargeable 3 V lithium-ion battery in the common 2032 coin cell format is demonstrated in a classroom environment without the use of expensive and complex air-free equipment. The procedure has been developed to eliminate the use of highly toxic materials and flammable solvents, can be accomplished in 15 min, and is designed to be as inexpensive, safe, and simple as possible. The battery can be repeatedly charged with a cheap USB-powered charger and can be used to power an LED te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“… Show by calculation that light in the visible spectrum has sufficient energy to generate current in a silicon solar panel. Silicon has a band gap of 1.14 eV at 302 K. Explore energy storage topics by constructing a rechargeable lithium-ion battery …”
Section: Chemistry Applicationsmentioning
confidence: 99%
“… Show by calculation that light in the visible spectrum has sufficient energy to generate current in a silicon solar panel. Silicon has a band gap of 1.14 eV at 302 K. Explore energy storage topics by constructing a rechargeable lithium-ion battery …”
Section: Chemistry Applicationsmentioning
confidence: 99%
“…Importantly, the need for a rigorous drying laboratory is crucial. , These issues set big barriers to prepare batteries in general chemistry laboratories. Several instructors have reported lithium ion coin cell fabrication without a glovebox, which decreases the experimental cost. Maharaj et al reported the assembly and testing of a rechargeable 3 V lithium ion battery in the common 2032 coin cell format as a demonstration in a classroom environment. However, the used electrolyte comprises lithium trifluoromethanesulfonate (LiO 3 SCF 3 , lithium triflate) in propylene carbonate solvent.…”
Section: Introductionmentioning
confidence: 99%
“…For example in the United States, the Next Generation Science Standards (NGSS) include systems thinking and modeling as a cross-cutting concept (4,5). Recently, a special issue of the Journal of Chemical Education that focused on systems thinking in chemistry education has provided a number of examples for chemistry topics that can be meshed with traditional content of the general chemistry curriculum (6)(7)(8)(9)(10)(11)(12)(13). While these articles provided a number of practical examples of content in general chemistry connecting to larger systems, the role of chemistry in the discovery and production of pharmaceuticals was not featured as an example.…”
Section: Introductionmentioning
confidence: 99%